WiMAX channel characteristic analysis and capacity estimation - Harng G.K.; Kiong T.S.; Koh J.; Yap D. (2023)
WiMAX (IEEE 802.16) is a broadband wireless access technology that enables convergence of mobile and fixed broadband networks through scalable OFDMA (Orthogonal Frequency Division Multiple Access) technology. This paper presents an analytical study of WiMAX propagation channel and estimates the channel capacity through simulation. WiMAX channel performance of different spectrum frequency bands applied in Asia Pacific region are investigated and evaluated in this paper.